DExMA: An R Package for Performing Gene Expression Meta-Analysis with Missing Genes - Juan Antonio Villatoro-García; Jordi Martorell-Marugán; Daniel Toro-Domínguez; Yolanda Román-Montoya; Pedro Femia; Pedro Carmona-Sáez (Mathematics, 2022)
Meta-analysis techniques allow researchers to jointly analyse different studies to determine common effects. In the field of transcriptomics, these methods have gained popularity in recent years due to the increasing number of datasets that are available in public repositories. Despite this, there is a limited number of statistical software packages that implement proper meta-analysis functionalities for this type of data. This article describes DExMA, an R package that provides a set of functions for performing gene expression meta-analyses, from data downloading to results visualization. Additionally, we implemented functions to control the number of missing genes, which can be a major issue when comparing studies generated with different analytical platforms. DExMA is freely available in the Bioconductor repository.